Third wave of COVID-19 pandemic in Africa: Challenges and recommendations. (August 2022) - Hemmeda, Lina; Shabani, Moshi Moshi; Kolawole, Barakat Olajumoke; Muhammad, Soima Ali; Fatima, Kaynat; Siddiqui, Amna; Rackimuthu, Sudhan; Yaqoob, Sadia; Elechi, Kelechi Wisdom; Abdallah Mohammed, Yousra Ibrahim
Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has evolved in different waves and is currently in its third wave for the majority of countries around the world. Each wave emanated with its own set of challenges. Lower- and middle-income countries such as most African countries have faced additional challenges compared to high-income countries. This paper highlights the challenges faced by Africa during the third wave of COVID-19 and proposes recommendations and strategies to contain the spread. We conducted a mini-review for the newly released articles and researches about the challenges faced by Africa during COVID-19. Fragmented healthcare sectors, limited healthcare resources and emergence of co-infections in COVID-19 patients, inadequate vaccination rollout and political conflicts are the major challenges faced by the African countries. Our recommendations to defeat this outbreak and subsequent pandemics is to raise the public's awareness about vaccines through campaigns and social media in order to lessen vaccine hesitancy. Governments as well should focus on under-served and vulnerable populations, patients with comorbidities, and communities living in endemic-striking settings as these people are more prone to the severe form of the disease. Moreover, by adopting socio-ecological perspectives, one can implement multi-level integrated interventions to help control COVID-19 more effectively.